Identifikasi Simplisia yang Dijual sebagai Strychnos ligustrina Bl. di Pasar Tradisional Surabaya dengan Metode Random Amplified Polymorphic DNA (RAPD) - Oeke Yunita; Angelica Kresnamurti (The East Java Biological Society, 2005)
Authentication of Strychnos ligustrina Bl. had been performed at molecular level (DNA) with Random Amplified Polymorphic DNA (RAPD) method, based on the amplification of random DNA fragments by Polymerase Chain Reaction (PCR) with a single arbitrary primer. The aim of this research was obtaining similar banding patterns between DNA of plant Strychnos ligustrina Bl. and DNA of its lignum on local market. Strychnos ligustrina Bl. was determined by UPT Balai Konservasi Tumbuhan Kebun Raya Purwodadi and plants sold as Strychnos ligustrina Bl. were collected as lignum from traditional market at Wonokromo, Rungkut, Genteng, Benowo dan Pabean. DNA from these plants were extracted by modified Cetyltrimethylammonium bromide (CTAB) method and amplified by RAPD method. Amplification had been performed by primer OPO-4 had shown banding patterns on the gel electrophoresis which banding patterns were shown by Strychnos ligustrina Bl. and plants sold as Strychnos ligustrina Bl. on Benowo. Based on this early result, we assume that plants sold as Strychnos ligustrina Bl. on Benowo has closely genetic relationship with Strychnos ligustrina Bl.